2016
DOI: 10.1002/ajpa.22966
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of dentognathic pathologies in the Dmanisi mandibles

Abstract: Objectives: Due to the scarcity of the fossil record, in-vivo changes in the dentognathic system of early Homo are typically documented at the level of individual fossil specimens, and it remains difficult to draw population-level inferences about dietary habits, diet-related activities and lifestyle from individual patterns of dentognathic alterations. The Plio-Pleistocene hominin sample from Dmanisi (Georgia), dated to 1.77 million years ago, offers a unique opportunity to study in-vivo changes in the dentog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 184 publications
1
23
0
Order By: Relevance
“…That said, all carious lesions ultimately share an etiology that is based on the presence of certain cariogenic bacteria and fermentable carbohydrates (Clarkson et al, 1987). Clearly, therefore, given the results of this and other recent studies (Grine et al, 1990;Trinkaus et al, 2000;Lanfranco & Eggers, 2012;Lacy et al, 2012;Humphrey et al, 2014;Lacy, 2014;Liu et al, 2015;Arnaud et al, 2016;Margvelashvili et al, 2016;Towle, 2019), cariogenic bacteria were prevalent in many, if not all, hominin species.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…That said, all carious lesions ultimately share an etiology that is based on the presence of certain cariogenic bacteria and fermentable carbohydrates (Clarkson et al, 1987). Clearly, therefore, given the results of this and other recent studies (Grine et al, 1990;Trinkaus et al, 2000;Lanfranco & Eggers, 2012;Lacy et al, 2012;Humphrey et al, 2014;Lacy, 2014;Liu et al, 2015;Arnaud et al, 2016;Margvelashvili et al, 2016;Towle, 2019), cariogenic bacteria were prevalent in many, if not all, hominin species.…”
Section: Discussionmentioning
confidence: 62%
“…In the hominin lineage it is often suggested that caries is a modern disease and is scarce or absent in past hominin groups, usually justified by inferring dietary or oral bacterial differences between present day and ancient hominin populations (Brothwell, 1963;Armelagos & Cohen, 1984;Hildebolt & Molnar, 1991;Tillier et al, 1995;Lanfranco & Eggers, 2012;Guatelli-Steinberg, 2016;Adler et al, 2017). However, evidence for the presence of carious lesions in a variety of non-agricultural hominin groups is growing (e.g., Grine et al, 1990;Trinkaus et al, 2000;Lanfranco & Eggers, 2012;Lacy et al, 2012;Humphrey et al, 2014;Lacy, 2014;Liu et al, 2015;Arnaud et al, 2016;Margvelashvili et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The lesion described here adds to the total number, as well as types of caries reported so far in fossil hominins-in this case 12 in P. robustus alone (Clement, 1956;Grine et al, 1990;Robinson, 1952;Towle, 2017). Because caries formation requires fermentable carbohydrates and cariogenic intra-oral bacteria (Clarkson et al, 1987), it is evident that both were present for at least the past 2.0-1.5 million years (Arnaud et al, 2016;Lacy, 2014;Trinkaus et al, 2000;Towle, 2017;Margvelashvili et al, 2016).…”
Section: [Figure 1 Here]mentioning
confidence: 99%
“…This is the case for many agricultural and huntergatherer diets, with specific cariogenic foods or tough non-cariogenic vegetation/meat (e.g., Novak, 2015;Vodanović et al, 2005;Slaus et al, 2011;Srejic, 2001;Varrela, 1991;Humphrey et al, 2014;Kelley et al, 1991;Lacy, 2014;Larsen et al, 1991). There is growing evidence that this relatively high caries rate is particularly characteristic of the Homo genus (e.g., Arnaud et al, 2016;Lacy, 2014;Lanfranco & Eggers, 2012;Lacy et al, 2012;Liu et al, 2015;Margvelashvili et al, 2016). Given that 12 caries have been described in P. robustus, it is likely that their diet was more similar to earlier Homo than once thought, at least to the extent that both consumed cariogenic foods.…”
Section: [Figure 1 Here]mentioning
confidence: 99%
See 1 more Smart Citation